2000
DOI: 10.1088/0964-1726/9/4/313
|View full text |Cite
|
Sign up to set email alerts
|

A new multi-function thin-film microsensor based on Ba1-xLaxTiO3

Abstract: A new multi-function microsensor with a barium lanthanum titanate (Ba1-xLaxTiO3) thin film is developed for the fabrication of a thin-film resistor and a metal-insulator-semiconductor (MIS) capacitor on a SiO2/Si substrate. The results reveal that the thin-film resistor has good sensitivity to visible light and good thermal sensitivity within the temperature range of 28-400 °C. The MIS capacitor is sensitive to changes in the relative humidity (RH), with a 130% change of the current for a humidity change from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Their electrical properties and hence sensing behavior can be modified easily by an appropriate substitution of cations at A and B sites of the oxide ABO 3 . At present thin and thick film of these oxides are being used for fabrication of multifunctional sensor [1][2][3]. Alkaline-earth stannates (ASnO 3 , where A = Ca, Sr, Ba) are also members of perovskite oxide family.…”
Section: Introductionmentioning
confidence: 99%
“…Their electrical properties and hence sensing behavior can be modified easily by an appropriate substitution of cations at A and B sites of the oxide ABO 3 . At present thin and thick film of these oxides are being used for fabrication of multifunctional sensor [1][2][3]. Alkaline-earth stannates (ASnO 3 , where A = Ca, Sr, Ba) are also members of perovskite oxide family.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 exhibit a negative temperature coefficient (NTC) and have good linearity and high sensitivity. The temperature coefficient of the film at 30 o C is -5.22% o C -1 under a test voltage of 1 V, which is similar to that of SrNb x Ti 1-x O 3 film (-4.36% o C -1 ) [1], and higher than that of Ba 1-x La x TiO 3 (-1.61% o C -1 ) [2] and Sr 1-x La x TiO 3 (-1.73% o C -1 ) [6]. The effect of test frequency on the impedance (Z) of the film resistor at different temperatures is depicted in Figure 5.…”
Section: Resultsmentioning
confidence: 67%
“…Perovskite-type oxides (ABO 3 ) attract much attention in recent years because these oxide are not only used as high-permittivity dielectric in non-volatile memory, but also can be used as sensing materials, moreover, sensing properties of these oxides may be modified by appropriate combination of cationic constituents. Our previous works [1,2] have found that even though both Ba 1-x La x TiO 3 and SrNb x Ti 1-x O 3 thin film have photo-, thermal and humidity sensitivity characteristics, photo sensing characteristics is better in La-doped film and thermal sensing characteristics is better in Nb-doped film. Therefore, in this work, Ba 1-x La x Nb y Ti 1-y O 3 (x=0.25%, y=0.25%) thin-film is proposed with a view to achieving better photo, thermal and humidity sensing properties.…”
Section: Introductionmentioning
confidence: 97%
“…SrNb x Ti 1−x O 3 and Ba 1−x La x O 3 thin films have demonstrated good sensitivity to visible light [6,7]. In this work, Ba 1−x Sr x Nb y Ti 1−y O 3 thin film is developed for the fabrication of thin-film resistors on SiO 2 /Si substrate to achieve supe-rior photosensing properties within a wide optical wavelength range.…”
Section: Introductionmentioning
confidence: 99%